Market based decarbonization and the interaction with reliability policies - Georg Thomaßen; Thomas Bruckner (Universität Leipzig, Institut für Infrastruktur und Ressourcenmanagement (IIRM), 2024)
This paper investigates market-based decarbonization, driven by carbon pricing, and under different regulatory settings. These consist of a conventional energy-only market (EOM), an EOM with operating reserve demand curve (ORDC) and a capacity market (CM). We find that contrary to previous research findings, all markets produce conclusive market outcomes in all stages of decarbonization, as flexible technologies create market signals that ensure the economic viability of renewables. This is relevant for systems that rely on carbon pricing, but also for those relying on out-of-the-market measures to deploy renewables, as it implies that markets can be deregulated again later if carbon prices are sufficiently high. All three regulatory scenarios further achieve close-to-optimal market outcomes, if they are calibrated well. The outcome in CMs, however, is especially prone to suboptimal configurations, relying on several design parameters, which are commonly deducted from weather data and system projections. Varying only one of these parameters induced large changes in the observed generation mix. ORDCs provided more stable results, even if the input parameters differed strongly from optimal values. We therefore recommend to rely on ORDCs to maintain resource adequacy, as they appear to produce lower costs and interfere less with the general market dynamics than CMs.
Keywords: 330